Experimenting with the use of persona in a focus group discussion with older adults in Malaysia - Hisham, S. (Association for Computing Machinery, 2009)
Eliciting user-requirements from older adults -- especially amongst non-users -- can be challenging. This is due to the fact that older adults are varied in term of their functional abilities and experience with technology. The common User-centered design (UCD) techniques such as focus group and interviews were found to be less effective with older adults. Inspired by the benefits of persona in enhancing designer's attention through narrative and storytelling, the study reported in this paper tested persona as a communication tool in a focus group discussion with older adults in Malaysia. The study was carried out to gather Malaysian older adults' needs and requirements for the development of a prototype email application. Findings and feedbacks from the study shows that persona can be a potential technique to be applied in working with older adults. The use of persona in a focus group discussion does not only benefit the researchers and designers but also the participants -- particularly in building interest among non-users to embrace computers.